From both sides now: crossover effects influence navigation in patients with unilateral neglect. - Punt, T; Kitadono, K; Hulleman, J; Humphreys, G; Riddoch, M (2008)
Unilateral neglect is a challenging disorder that pervades a range of behaviours following stroke and hampers recovery. Although a preponderance of clinical studies measure performance on a range of bedside assessments, including line bisection and cancellation tasks, there have been calls for studies to embrace more relevant functional measures. Here, for the first time, we present data from two separate tasks that characterise the performance of seven patients with unilateral neglect when navigating a power wheelchair. The tasks involved negotiating an obstacle course and steering a central path between gaps of different sizes. Results from the obstacle course confirmed the clinical observation and predicted bias of contralesional errors. However, the second task revealed a robust "crossover" effect. Patients deviated to the ipsilesional side for large gaps but deviated increasingly contralesionally when steering through small gaps in behaviour that was analogous to that previously shown on line bisection tasks. Contrary to being seen as an unintuitive finding, further analysis of these errors suggests that patients are giving disproportionate weight to the location of the ipsilesional object when plotting a midline course between two objects. Our results provide a platform for further studies to investigate the modulation and rehabilitation of this important skill.